PERSEPSI MASYARAKAT TERHADAP PENDIDIKAN PESANTREN DI ERA DIGITAL : ANTARA KEPERCAYAAN DAN STIGMA - Nabila Mawaddah (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to examine the community's views on the behavior of Islamic boarding school children today, especially those who deviate from Islamic teachings. The focus of the discussion is social phenomena that are in the public spotlight, such as the controversial actions of Islamic boarding school figures which went viral on social media. The research method used is literature study by analyzing various sources of literature and related news. The results of the research show that people are starting to question the credibility of some Islamic boarding school children because their behavior does not reflect Islamic values. This phenomenon shows the need to evaluate and strengthen moral education in the Islamic boarding school environment so that it remains a center for Islamic character formation.